DIRECTIONS FOR STRENGTHENING THE COMPETITIVENESS OF HOTEL AND RESTAURANT BUSINESS ENTERPRISES IN MODERN CONDITIONS (Development Service Industry Management, 2025)
The study focuses on the issues of forming and strengthening the competitive positions of hotel and restaurant business entities in Ukraine in today's difficult socio-economic conditions. anti-crisis management of business entities with a view to ensuring adaptation and forming an appropriate level of economic security of business in turbulent conditions. The purpose of the study is to further develop methodological and applied principles for strengthening the competitiveness of hotel and restaurant businesses in modern Ukrainian realities. Promising areas and directions for further development of hotel and restaurant businesses are substantiated. The strategy and institutional support for the development of hotel and restaurant business entities, including on an innovative basis, have been developed. An organizational and economic mechanism for activating the economic activity of hotel and restaurant business enterprises has been formed. The directions of implementation of the management and infrastructure mechanism for the growth and development of hotel and restaurant business entities are determined. Ways and means of improving the resource provision of economic activities in the hotel and restaurant business are substantiated. Coordination of the management of the development of hotel and restaurant business entities with modern trends in globalization and the functioning of the domestic domestic market has been ensured. The innovative activity of the tourist enterprises is evaluated, as well as the quality of management in this area; the tools to boost further innovation activity are suggested. The prospective areas and directions of innovative development of the tourist enterprises are substantiated. The provisions of the strategy and the institutional background for the development of the tourism enterprises on an innovative basis are offered. The organizational and economic mechanism of activating the innovation activity of the tourist enterprises has been formed. The directions of implementing the administrative-infrastructure mechanism of innovative development of the tourism enterprises are determined. The ways and means of intellectual and personnel support of innovative tourism activity are grounded. The coordination of management of the tourist enterprises innovative development with the modern tendencies of globalization and functioning of the world tourism market is ensured.
Keywords: enterprise management; hotel and restaurant business; management; competitiveness; policies for the formation; strengthening and implementation of competitive advantages